Implementation of grid computing infrastructure in FCSIT - Azwani, Mustaffa (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Grid computing is a incredibly powerful and effective computing solution in today's complex world of computational power. The demand for a very high speed machine processing capabilities has lead to the emerging of grid computing technology. Distinguished from the conventional distributed computing technology, grid computing focus on large-scale resources sharing among heterogeneous computing environment. It is basically a technology that enables users to spread the computing resources across a number of machines. Implementing grid environment is quite a challenging task. The Globus toolkit, which is used to implement the grid, need supporting softwares in order for it to works. A grid service, which is a type of web service, will be used to run the grid. This grid service can be develop depends on the users need. If all goes well users can enjoy the beauty of grid.